The Effect of Internal Audit Quality on Financial Accountability Quality at Local Government - Zeyn, Elvira (Journal of Accounting, Business and Finance Research, 2018)
The need for local government audit is actually based on the demands of public accountability to the government by the public entity in order to realize the creation of good governance (good government governance). The role of government internal audit is an important management function in governance both at central and local government. Government internal audit quality is very important, because the internal audit quality will improve the financial accountability that will be produced reliable financial reports as a basis for decision making by the stakeholder's. There are many factors influencing financial accountability quality, including internal audit quality. Based on this background, this research has been aimed to study: (1) the effect of internal audit quality on financial accountability quality. This research uses survey method with description verification approach and type of causal research, conducted on 36 Inspectorate Local Government in West Java and Banten as the unit of analysis, while the unit of observation is a Team Audit such as, Inspector, Inspector of area, audit team leader and members of audit team. The type of data is primary data collected by a questionnaire research instruments containing ordinal scale for measurement. Validity and reliability tests have also been done on the entire collected questionnaire. Furthermore, data are converted into interval scale, then hypothesis test are done using Regression.